Chapter Da Firenze al mare: Leonardo e l'Arno tra ingegneria idraulica e visione territoriale - Chiti, Michela (Territori, 2023)
The vision related to the territorial project of the navigable canal, which was supposed to connect the cities of Florence, Prato and Pistoia and, passing through the Nievole Valley, reach the Arno and then the sea, stems from the study of some drawings by Leonardo da Vinci, dating from around 1503-1504. The article retraces the reading of the various signs found, in which there appears to be a mixture between the dimension of cartographic survey and the project idea, in a dialectic between territorial potential and criticalities, according to the multidisciplinary approach to territorial science that was explored by Leonardo.